A Brief Review of Processing, Structure, Properties, and Sustainability of Artificial Silk Fibers. Issue 10 (3rd October 2022) - Comish, Ella; Lester, Rosie; Shah, Darshil U.
ABSTRACT: Silk spinning has evolved many times in nature enabling a variety of organisms to produce fibers boasting exceptional properties, notably high strength, and toughness, through energy- and resource-efficient processes. This has motivated scientists to both understand natural silk spinning processes, and replicate such processes or create new processes to produce artificial silks for a range of applications, from biomedicine to engineering. In this literature review, we briefly present some natural silk production processes, and compare these to various approaches to processing artificial silks. The artificial silk processing methods we discuss use natural, recombinant, or regenerated silk proteins as dope to then wet, microfluidic, dry, or electro-spin the filaments. We critically evaluate the structure and properties of the resultant artificial silks to natural silks. We then examine the sustainability of artificial silks, in comparison to natural silks, which are model eco-fibers, and other technical fibers, to encourage fore-thinking in the design of artificial silk production processes. A discussion on the future challenges in artificial silk production processes follows. This brief review is for an audience with limited prior knowledge on natural and artificial silks, but with some basic understanding of materials science.